Importance of Biochemical Markers in Postmenopausal and Senile Osteoporosis - Deniz Evcik; Mustafa Serteser (Galenos Yayinevi, 2002)
Recently, the biochemical markers are widely used in order to evaluate the bone turnover. This study was planned to investigate the role of biochemical markers and Bone Mineral Density(BMD) in postmenopausal (PMO) and senile osteoporosis (SO) patients. A total of 86 patients( 44 PMO, 42 SO), ages ranged between 39-79 were included in this study. Alkaline phosphatase (ALP) and osteocalcin levels were determined from blood samples. Urinary deoxypyridinoline(Dpd) and creatinine(cr) concentration were examined and the ratio of Dpd/cr was calculated. Also BMD of the patients were measured from L1-L4 and proximal femur and t score were determined. There was no statistical difference in ALP levels between two groups. Osteocalcine and Dpd/cr levels were statistically increased in PMO group(p<0.001). According to BMD t score which was measured from proximal femur was significantly higher in SO patients(p<0.05). Our results show that biochemical markers are useful for the assessment of high-turnover osteoporosis.